The collision detection algorithm based on bounding volumes and space subdivision - Zhiliang Liu; Desheng Zhang (2011 International Conference on Image Analysis and Signal Processing, 2011)
In this paper, we propose a collision detection algorithm that combines bounding volumes and space subdivision to solve collision and self-collision detection of deformable objects. First, we use the AABB bounding volumes method to eliminate the objects that cannot intersect. Second, we use the space division method to detect the objects that can collide. The method employs hash function as data structure, and tetrahedron meshes as the primitives. Finally we experiment with the parameters of the algorithm, such as hash function, hash table size, and spatial cell size. The algorithm has been implemented based on the tetrahedron, however, it can handle other object primitives.